Utilization of Reading Corners to Improve Literacy Skills of Grade II Students Through the Teaching Campus Program - Anu, Maria Susanti; Dhiu, Konstantinus Dua; Juita, Angelina Kurnia; Ngura, Elisabeth Tantiana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This study was conducted based on the low reading literacy culture and some grade II students who still have difficulty reading. One of the school literacy movement programs that can be done to increase students' interest in reading is the Reading Corner program. The purpose of this study was to determine the role of the reading corner on students' interest in reading. The type of research used in this study is descriptive qualitative, with research methods in the form of observation, interviews, and documentation. The subjects of the study were grade II students of SDK Piga, the object of this study was the reading corner in grade II. The results of the study showed that the reading corner plays a very important role in growing and increasing students' interest in reading at school. Based on the study, it can be concluded that with a reading corner, students can use the reading corner as the closest reading facility, as the closest reading material, and also as a comfortable and attractive place to increase interest in reading. The reading corner is managed by teachers and students who aim to introduce students to fun learning resources.